Water-Food-Energy-Environment nexus science policy dialogue at subnational level to guide future adaptation scenarios in Morocco - Kertolli Emirjona; Belhouchette Hatem (2023)
As we move closer to sustainability and improving adaptive methods, we're also focusing on addressing the current knowledge gaps, where the ongoing communication between science and policy emphasizes the dedication to convert knowledge into practical solutions.